High Diazotrophic Diversity but Low N2 Fixation Activity in the Northern Benguela Upwelling System Confirming the Enigma of Nitrogen Fixation in Oxygen Minimum Zone Waters - Reeder, Christian Furbo; Arévalo-Martínez, Damian L.; Carreres-Calabuig, Joan A.; Sanders, Tina; Posth, Nicole R.; Löscher, Carolin Regina (Frontiers in Marine Science, 2022)
Oxygen minimum zones (OMZs) have been suggested as a suitable niche for the oxygen-sensitive process of biological fixation of dinitrogen (N2) gas. However, most N2 fixation rates reported from such waters are low. This low N2 fixation activity has been proposed to result from the unusual community of N2 fixers, in which cyanobacteria were typically underrepresented. The Northern Benguela Upwelling System (North BUS) is part of one of the most productive marine ecosystems and hosts a well-developed OMZ. Although previous observations indicated low to absent N2 fixation rates, the community composition of diazotrophs needed to understand the North BUS has not been described. Here, we present a first detailed analysis of the diazotrophic diversity in the North BUS OMZ and the Angola tropical zone (ATZ), based on genetic data and isotope speciation. Consistent with a previous study, we detected a slight N deficit in the OMZ, but isotope data did not indicate any active or past N2 fixation. The diazotroph community in the North BUS was dominated by non-cyanobacterial microbes clustering with members of gamma-proteobacteria, as is typical for other OMZ regions. However, we found a strikingly high diversity of Cluster III diazotrophs not yet described in other OMZs. In contrast to previous observations, we could also identify cyanobacteria of the clades Trichodesmium sp., UCYN-A and Cyanothece sp., in surface waters connected to or above the OMZ, which were potentially active as shown by the presence of genes and transcripts of the key functional marker gene for N2 fixation, nifH. While the detection of diazotrophs and the absence of active N2 fixation (based on isotopic speciation) are consistent with other OMZ observations, the detected regional variation in the diversity and presence of cyanobacteria indicate that we still are far from understanding the role of diazotrophs in OMZs, which, however, is relevant for understanding the N cycle in OMZ waters, as well for predicting the future development of OMZ biogeochemistry in a changing ocean.